2012
DOI: 10.1002/nag.1134
|View full text |Cite
|
Sign up to set email alerts
|

Two methods for pore network of porous media

Abstract: SUMMARYTwo approaches of generating pore networks of porous media are presented to capture the pore fabric. The first methodology extracted pore structure from a computer simulated packing of spheres. The modified Delaunay tessellation was used to describe the porous media, and modified Nelder-Mead method in conjunction with three pore-merging algorithms was used to generate the pore size and coordination number distributions of the randomly packed spheres. The Biconical Abscissa Asymmetric CONcentric bond was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 37 publications
(41 reference statements)
1
56
0
1
Order By: Relevance
“…All these parameters can be extracted directly from packed spheres . Gao et al (2011) showed that both the pore size distribution and the coordination number distribution approximately obey normal distribution for the random close packing of particles. There is no direct proof that the pore bodies are spatially correlated in size; however, there is weak spatial correlation between the pore body size and coordination number.…”
Section: Network Descriptionmentioning
confidence: 97%
See 4 more Smart Citations
“…All these parameters can be extracted directly from packed spheres . Gao et al (2011) showed that both the pore size distribution and the coordination number distribution approximately obey normal distribution for the random close packing of particles. There is no direct proof that the pore bodies are spatially correlated in size; however, there is weak spatial correlation between the pore body size and coordination number.…”
Section: Network Descriptionmentioning
confidence: 97%
“…The procedure for constructing an equivalent network is presented in Gao et al (2011). The main geometric and topological parameters that can be considered in the network include total number of pores in the network, average pore size, maximum and minimum pore size, standard deviation of pore size, pore spacing, parameters for characterizing the BACON bonds connecting two neighboring pores, average coordination number, standard deviation of coordination number.…”
Section: Network Descriptionmentioning
confidence: 99%
See 3 more Smart Citations